2019
DOI: 10.13057/biodiv/d201012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oils of Thymelaea hirsuta from Algeria

Abstract: Abstract. Souhila B, Takia L, Messaoud R, Pierre C, Gilles F. 2019. Chemical composition and antibacterial activity of essential oils of Thymelaea hirsuta from Algeria. Biodiversitas 20: 2868-2876. The objectives of this study were to determine the chemical composition and to evaluate the antibacterial activity of Thymelaea hirsuta (L.) Endl., essential oils from seven sampling locations in M'sila region (Algeria). Extraction of essential oils was carried out by the hydro-distillation; the analysis of chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, Jalayar et al 33 reported that the methanol extract of Anacyclus pyrethrum has an inhibitory effect on Escherichia coli at the concentrations from 300 to 1000 mg/mL with a value of MIC and MBC corresponding to 800 mg/ mL. According to previous study 19,34 , the absence of antimicrobial activity does not mean that the bioactive compounds are not present in the plant or the plant has no antimicrobial activity against microorganisms since various factors such as the dose of solvent used in the extraction of metabolites, the extraction time and rotary evaporator used during extraction of crude also trigger influence on the activities of crudes (the temperature used)…”
Section: Table 1: Phytochemical Screening Of the Methanol Extractsmentioning
confidence: 96%
“…Furthermore, Jalayar et al 33 reported that the methanol extract of Anacyclus pyrethrum has an inhibitory effect on Escherichia coli at the concentrations from 300 to 1000 mg/mL with a value of MIC and MBC corresponding to 800 mg/ mL. According to previous study 19,34 , the absence of antimicrobial activity does not mean that the bioactive compounds are not present in the plant or the plant has no antimicrobial activity against microorganisms since various factors such as the dose of solvent used in the extraction of metabolites, the extraction time and rotary evaporator used during extraction of crude also trigger influence on the activities of crudes (the temperature used)…”
Section: Table 1: Phytochemical Screening Of the Methanol Extractsmentioning
confidence: 96%